2006
DOI: 10.1073/pnas.0604150103
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding to the HCCH motif of HIV-1 virion infectivity factor induces a conformational change that mediates protein–protein interactions

Abstract: Virion infectivity factor (Vif) is an accessory protein encoded by HIV-1 and is critical for viral infection of the host CD4 ؉ T cell population. Vif induces ubiquitination and subsequent degradation of Apo3G, a cytosolic cytidine deaminase that otherwise targets the retroviral genome. Interaction of Vif with the cellular Cullin5-based E3 ubiquitin ligase requires a conserved BC box and upstream residues that are part of the conserved H-(Xaa)5-C-(Xaa)17-18-C-(Xaa)3-5-H (HCCH) motif. The HCCH motif is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 49 publications
2
94
2
Order By: Relevance
“…Vif binds EloC through its BC box region (residues 144 SLQYLA 149 ) (13)(14)(15)(16), which mimics the conserved cellular interface of SOCS box proteins. The interaction between Vif and Cul5 is primarily mediated by a novel zinc-binding motif (H 108 C 114 C 133 H 139 ) upstream of the Vif BC box (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Vif binds EloC through its BC box region (residues 144 SLQYLA 149 ) (13)(14)(15)(16), which mimics the conserved cellular interface of SOCS box proteins. The interaction between Vif and Cul5 is primarily mediated by a novel zinc-binding motif (H 108 C 114 C 133 H 139 ) upstream of the Vif BC box (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…HIV-1 viral infectivity factor (Vif) is essential for viral infectivity because it recruits the host restriction factor APOBEC3G (A3G) to the E3 ligase complex, which consists of the scaffold protein Cullin5 (CUL5) and substrate adaptors Elongin B/C and Rbx, to induce A3G polyubiquitination and degradation, thereby suppressing A3G-mediated antiviral activity (6,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Recent studies have shown that the transcription cofactor core-binding factor subunit beta (CBF-␤) is a key factor in Vif function (29,30).…”
mentioning
confidence: 99%
“…Vif may also inhibit APOBEC3 activity through mechanisms independent of proteasomal degradation (17,18,27,36,46). Vif associates with the Cul5-EloB-EloC complex by binding directly to EloC via a BC box motif at positions 144 to 153 and to Cul5 via hydrophobic residues at positions 120, 123, and 124 within a zincbinding region (residues 100 to 142) formed by a conserved H-X 5 -C-X 17-18 C-X 3-5 -H (HCCH) motif and a recently identified Vif cullin box (26,28,33,45). Vif binding to A3G and A3F is essential for their degradation by the Vif-Cul5 E3 ligase (25,27,29).…”
mentioning
confidence: 99%